ANALYSIS OF PROFITABILITY RATIOS OF WINERIES IN THE MARAMURES REGION - Lucica Armancă (Agricultura)
The aim of the research is to identify a sustainable wine-growing system of the Maramures Region based on the values of some indicators of profitability ratios. The research is carried out on the global activity of the companies having as their scope of business "Cultivation of grapes / Manufacture of wine from grapes". Gathering information from the websites of the Romanian wine cellars as well as from the promotion website of the Romanian wine cellars ( www.cramaromania.ro) documentation based on financial accounting and bookkeeping information for the period 2019-2023 ( www.listafirme.ro ), then the application of the formulas of calculation of the researched indicators have allowed the presentation of some conclusions for the research results.